2020
DOI: 10.3390/jcm9040925
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Quality of Life and Nasal Polyp Size in Patients Suffering from Chronic Rhinosinusitis without Nasal Polyps, with Nasal Polyps or Aspirin-Exacerbated Respiratory Disease

Abstract: Chronic rhinosinusitis (CRS) is a common disease that substantially impairs the quality of life (QoL). Here, we aimed to assess patients' QoL in different subtypes of CRS and correlated this with nasal polyp size to improve the clinical understanding of the burden of disease. In this retrospective single-center study, 107 patients with the following diagnoses were analyzed: CRS without nasal polyps (CRSsNP), CRS with nasal polyps (CRSwNP), or aspirin-exacerbated respiratory disease (AERD). Sino-Nasal Outcome T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…Lin et al 1350 found that patients with moderate‐to‐severe asthma displayed worse sinus disease than those with mild asthma, with significantly higher mean CT‐scores. Subsequently, the association of both asthma and CRSwNP have also been related to an impaired QoL and loss of productivity 1351–1353 . Alobid et al 1354 showed that the QoL in patients with CRSwNP was worse with concomitant asthma mainly on physical functioning, body pain, and vitality.…”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 99%
“…Lin et al 1350 found that patients with moderate‐to‐severe asthma displayed worse sinus disease than those with mild asthma, with significantly higher mean CT‐scores. Subsequently, the association of both asthma and CRSwNP have also been related to an impaired QoL and loss of productivity 1351–1353 . Alobid et al 1354 showed that the QoL in patients with CRSwNP was worse with concomitant asthma mainly on physical functioning, body pain, and vitality.…”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 99%
“…Bars represent mean values with standard deviation (SD). Significance is displayed in figures *p ≤ 0.05, **p ≤ 0.01, ***p ≤ 0.001, ****p ≤ 0.0001, ns not significant symptoms [9]. The fact that they only observed significant differences between those two groups with regard to the single item "difficulty to smell or taste" but not in the other two above-mentioned items may be due to the fact that no stratification according to gender was performed.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of factors including genetics, epigenetics, hormones, immune function, and behaviour might be influenced by patients’ sex and gender identity [ 2 ]. CRS is a highly prevalent disease and especially phenotypes with nasal polyps and AERD can significantly impair patients’ QoL [ 9 ]. Although the impact of sex in CRSwNP and AERD is not yet fully elucidated, studies evaluating e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been shown that nasal polyposis might have a variable impact on HRQoL 27 and that patients with CRSwNP present a different HRQoL pro le compared to those with CRSsNP 28 .…”
Section: Discussionmentioning
confidence: 99%